Physical exercise and functional fitness of older adults in day care center - Dias, Claúdia (2019)
Poster presented at the 2nd International Congress of CiiEM - Translational Research and Innovation in Human and Health Science. 11-13 June, 2017, Campus Egas Moniz, Monte de Caparica, Portugal.